CELLULAR STRUCTURE FORMATION IN PUFFED RICE CAKES USING SEM ANALYSIS - VENKATACHALAPATHY NATARAJAN, NIKITHA MODUPALLI and (The Journal of Research, PJTSAU, 2019)
The increase in the trend of breakfast cereal and convenience food has raised the stage for several innovations to serve the need. Puffing is a very traditional and old practice of processing cereal grains that form light, fluffy, crispy product that are highly consumeracceptable. Puffed rice cakes are novel food products that have been recently added to breakfast cereals. There is accumulation of individually puffed grains to form a disc or biscuit like shape. The novelty of this product is that the disc shape is maintained by the grain without addition of any binding agents. Puffing is an instantaneous process which occur in few seconds at high temperatures to form light, fluffy expanded product that is crunchy and have good consumer acceptance. During the formation, puffing of grains occur upon rapid heating of the platens of mould due to which the unbound moisture gets evaporated and nucleates to form small gas cells. These gas cells increase in size as the temperature increases the volume till the vapour pressure is nullified by the pressure exerted by solid matrix. The SEM analysis showed the microstructural changes occurred in the rice cakes during the formation. It showed struts and nodes with closed air pockets. The changes in the rice cake during formation were observed at every 0.5 second from 1 to 4 seconds which showed the formation of bubbles and the air cells.